Impact of Islamic work ethics on civil servants’ performance: Mediating effect of work engagement - Zaenal Arifin Sahabuddin; Abdul Talib Yunus; Rashid Ating; Muhammad Ashoer (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — This research focused on examining the influence of Islamic work ethics on work engagement and performance among civil servants in Indonesia. Moreover, the study explored the mediating effect of work engagement.Method — For this study, Muslim civil servants working in Makassar, Indonesia were selected as participants. To enhance the precision of the results, specific criteria for the respondents were established, including: (1) Civil servants holding a permanent position (including honorary roles); and (2) civil servants with a minimum of three years of work experience. A total of 150 responses were obtained. The survey was conducted using Google Forms, and the data was analyzed using Structural Equation Modeling (SEM) or Partial Least Square (PLS) PLS-SEM Version 3.0.Result — Islamic work ethics positively and significantly influence the work engagement and performance of civil servants in South Sulawesi. Concurrently, work engagement positively and significantly impacts the performance of these civil servants. Additionally, work engagement serves as a significant mediator in the relationship between Islamic work ethics and performance.Novelty — This research utilized Islamic work ethics derived from Islamic perspective literature to examine their influence on work engagement and performance among civil servants in Indonesia. Furthermore, the study investigated the mediating role of work engagement to determine its significance in the context of public service.